PENGARUH METODE SILABA TERHADAP KEMAMPUAN MEMBACA PERMULAAN SISWA KELAS I SDN PETEMON SURABAYA - Aulia Dewi, Yumnafiska; Larasati, Diyas Age; Yuliana, Leni (Jurnal PENEROKA: Kajian Ilmu Pendidikan Bahasa dan Sastra Indonesia, 2023)
This research is motivated by the low score achieved by students in the beginning reading ability in the Indonesian language subject. One way that can be used to overcome this problem is to apply the syllabus method. The purpose of this study was to describe the effect of the silaba method on the reading ability of first grade students at SDN Petemon Surabaya. The type of research used in this research is quantitative research using experimental methods, with the type of Pretest-Posttest Control Group Design. This study used the firstclass population at SDN Petemon Surabaya. Two classes were selected using a random sampling technique by lottery as the research sample. Class I-C consists of 25 students as an experimental class. Class I-A consists of 25 students as the control class. The instrument of this study used observation sheets and questions (pretest and posttest) in the form of literacy, totaling 5 questions. The data collection technique uses scoring on the results of observations and pretest and posttest assessment standards. The tests used were the normality test, homogeneity test and the T test were used to test the results of the research data. The results of the research data showed that the posttest average of the experimental class was , which was higher than the control class, which was . The results of the data using the t-test. The results of calculating t Count obtained a value of  followed by looking for a t table based on the df value of 48 with a level value of  showing a result of . This proves that there is an influence of the silaba method on the beginning reading ability of first grade students at SDN Petemon Surabaya.